Conservation Biology of Amphibians of Asia, Status of Conservation and Decline of Amphibians : Eastern Hemisphere - Das, Indraneil; Heatwole, Harold (Natural History Publications (Borneo) Sdn. Bhd., 2014)
There are several outstanding treatises of amphibian biology. “Biology of Amphibians” (Duellman and Trueb 1986) is an excellent general work, clearly written and well illustrated, and with a remarkable depth and breadth for a single volume. It will be the standard general reference on amphibians for many years to come and the present generation of herpetologists will consider it the “amphibian bible” much as their predecessors regarded G.K. Noble’s (1931) “The Biology of the Amphibia”. No single volume, however, fulfils the need for a sequential, monographic treatment of specialized topics.